Critical Thinking: The basics - Hanscomb, Stuart (London Routledge, 2023)
Critical Thinking: The Basics is an accessible and engaging introduction to the field of critical thinking, drawing on philosophy, communication, and psychology. Emphasising its relevance both to academic literacy and to decision-making in a range of contexts, this book introduces and explains the knowledge, methods, and skills needed to identify and avoid poor reasoning, reconstruct and evaluate arguments, and engage constructively in dialogues.
Keywords: Humanities; Philosophy; Psychology